The foundations and future of public law : essays in honour of Paul Craig - Fisher, Elizabeth (Elizabeth Charlotte); King, Jeff, 1973-; Young, Alison L.; Craig, Paul (Law) (Oxford : Oxford University Press, 2020)
In this collection, leading figures in UK and EU public law address seismic changes the field and reflect upon the implications of these changes, the fundamentals of public law, and the interrelationship between them across six themes: legislation, case law, theory, institutions, process, and constitutions.
Festschrift for Paul Craig.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 26, 2020).
Keywords: Public law; Law; Laws of specific jurisdictions & specific areas of law